Plan proyecto del Distrito de Barva - Carvajal-Chaves, Cristina (Instituto Tecnológico de Costa Rica., 2019)
The recovery of urban centers has become a strategy to improve the quality of life of human settlements. The challenge is that each urban center has a different context, so it is essential to study it in depth to understand its dynamics and thus do not become abandoned spaces. The conditions presented by an urban center will depend on whether it is a new or historical space, in the case of the latter, the application of the terms historical center, historical complex, cultural heritage, urban-historical landscape and cultural significance must be considered. As well as the analysis of the types of urban interventions such as revitalization, renovation and rehabilitation, so that the most convenient for the site can be carried out. Barva is the central district of the Heredian canton with the same name, and represents an urban settlement originated in the colonial era. Over time the district has extended its urban space in an uncontrolled manner, putting natural areas and the quality of life in the center of the canton at risk. Generating urban proposals that integrate the different variables that make up Barva becomes key to promoting sustainable urban development. Therefore, the reactivation of heritage, public space and the local economy is promoted, without forgetting the implication of the environment, mobility and urban treatments. It is important that urban intervention consider the goals at the country level to improve urban centers, which is why in this case we work with the Reglamento de Renovación Urbana, through the Plan Proyecto chapter as a guide for the structure of the proposal.
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2019.
Keywords: Barva Heredia; Centros históricos; Patrimonio arquitectónico; Planeamiento urbano; Proyectos arquitectónicos